WHISTLEBLOWING INTENTION OF FINANCIAL KEEPERS IN EDUCATION ORGANIZATION - Natawibawa, I Wayan Yeremia; Irianto, Gugus; Roekhudin, Roekhudin (Jurnal Aplikasi Manajemen, 2019)
The objective of this research was to examine the effect of organizational commitment and fraud severity rate on whistleblowing intention of financial keepers in school organization and to understand this relationship through prosocial organizational theory. The research population was 214 persons comprising of 24 principals, 97 vice-principals, 22 school administration heads, 32 treasurers, and 39 financial administration staffs in Public Senior/Vocational/Moslem High Schools in Malang City. Census sampling technique was used. Data were collected with a questionnaire. The return rate was 89.72%, meaning that there are 192 questionnaires returned and filled. Multiple regression instrument was used to analyze the data. The result shows that the unstandardized coefficients rate of organizational commitment is valued at -0.197 with a significance value of -0.002, while that of fraud severity rate is 0.768 with a significance value of 0.000. The conclusion was that organizational commitment has a negative effect on whistleblowing intention, whereas fraud severity rate has a positive effect on whistleblowing intention. It was suggested that the next research should use education organization at another level as a research object. Other variables or theories can be possibly used to create a better model of multiple linear regression.